Pengaruh Dukungan Rekan Kerja Terhadap OCB Dengan Kepuasan Kerja Sebagai Pemediasi Pada Karyawan Grage Jogja Hotel - Ignatius Soni Kurniawan; Herlin Laela Naeni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This study aims to determine the effect of co-worker support on organizational citizenship behavior (OCB) with job satisfaction as a mediating variable. The population in this study were employees of the Grage Jogja Hotel. The sampling technique uses saturated samples. Data were analyzed by multiple linear regression analysis. The findings show that job satisfaction is able to mediate the relationship between co-workers support for OCB. The findings have implications for company leadership to increase co-worker support items and low job satisfaction so that employee OCB will increase